2019
DOI: 10.5114/wiitm.2019.85177
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal laparoscopic surgery in large adrenal masses.

Abstract: Introduction: The laparoscopic adrenalectomy (LA) has become the gold standard since the transperitoneal laparoscopic approach was first reported. Aim: To evaluate the applicability, safety and short-term results of laparoscopic surgery in adrenal masses over 6 cm. Material and methods: Demographic data, hormonal activities, imaging modalities, operative findings, operation time, conversion rates, complications, duration of hospital stay and histopathologic results of 128 patients who underwent laparoscopic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Additionally, the limited retroperitoneal space can cause interference and collision of surgical instruments, increasing the difficulty of exposing and isolating the adrenal lesion ( 15 ). Hence, surgeons prefer the transperitoneal approach for large adrenal masses because there is more working space ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the limited retroperitoneal space can cause interference and collision of surgical instruments, increasing the difficulty of exposing and isolating the adrenal lesion ( 15 ). Hence, surgeons prefer the transperitoneal approach for large adrenal masses because there is more working space ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of a large size adrenal tumour varies widely among different studies, ranging from ≥5 cm to ≥8 cm. [ 5 14 15 ] Based on the final pathology report, we defined LTs as the largest diameter of tumours ≥6 cm. Diagnostic modalities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple comparative studies have demonstrated that minimally invasive surgery is a safe and feasible method for large adrenal tumours compared with small ones. [ 4 8 9 14 15 17 ] LTs may be associated with increased intraoperative blood loss and conversion rate,[ 7 8 ] prolonged operative time[ 17 18 ] and longer hospital stay for transperitoneal LA. [ 7 19 ] In our study, although the operation time and bleeding amount were higher in LTs, the conversion rate, blood transfusion requirement, hospital stay and complication rates were similar between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…LA has been considered a substitute for traditional open surgery in the past decade by numerous studies [5][6][7][8]. Moreover, a study showed that laparoscopy was also safe and feasible for the treatment of large adrenal tumors [31]. However, the increase in the incidence rate of obesity, which is generally considered a major factor for increasing complications, particularly wound and septic complications [30], poses new challenges to LA.…”
Section: Discussionmentioning
confidence: 99%